An overview on synthesis, stability, opportunities and challenges of nanofluids. (2021) - Urmi, Wajiha Tasnim; Rahman, M.M.; Kadirgama, K.; Ramasamy, D.; Maleque, M.A.
Abstract: Nanofluids are the novel class of nanomaterials suspension in base fluids. A nanoscale colloidal dispersion which containing nanoparticles is called nanofluids. Nanofluids have shown enormously distinctive features, unique properties by offering the unexampled possibility for many applications. Nanofluids are a new generation of heat transfer fluids that have attracted researchers' attention from diverse fields due to their anomalous thermal behaviour and potential applications. Improved thermophysical properties of nanofluids including the thermal conductivity, viscosity, diffusivity, heat transfer coefficient are the most fundamental properties of nanofluids in the field of nanotechnology. Among all of the exciting properties of nanofluids, long-term stability is the first basic requirement in nanofluid research for maintaining their enhanced and outstanding thermophysical properties. This paper provides the ongoing advancement on the investigation of nanofluids including the preparation method, approaches to improve the stability, the assessment technique for the stability focusing challenges and opportunities of further improvement towards the performance of nanofluids.